2020
DOI: 10.1155/2020/6276803
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Investigation on the Influence of In‐Plane Damage on the Out‐of‐Plane Behavior of Masonry Infill Walls

Abstract: is study presents a finite element model to investigate the bidirectional seismic behavior of masonry infill walls. e test data are utilized to verify the numerical model. e comparison between the analytical and the experimental results indicates that the finite element model can successfully predict the failure mode, stiffness, and strength of the masonry infill wall. Based on the model, the effects of aspect ratio (height to length), slenderness ratio (height to thickness), and masonry strength on the out-of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…more than 50% for an IP drift of 0.15% for a wall with a slenderness ratio of 16) which is not convincing when compared to experimental results. Wang et al (2020) concluded that the reduction of OoP strength due to IP damage is influenced by slenderness ratio, aspect ratio, and additionally by the masonry strength which was not previously considered by others. The strength reduction was lower for masonry infills with higher compressive strength but the stiffness decay was found not affected by the masonry strength.…”
Section: Introductionmentioning
confidence: 85%
See 3 more Smart Citations
“…more than 50% for an IP drift of 0.15% for a wall with a slenderness ratio of 16) which is not convincing when compared to experimental results. Wang et al (2020) concluded that the reduction of OoP strength due to IP damage is influenced by slenderness ratio, aspect ratio, and additionally by the masonry strength which was not previously considered by others. The strength reduction was lower for masonry infills with higher compressive strength but the stiffness decay was found not affected by the masonry strength.…”
Section: Introductionmentioning
confidence: 85%
“…A comparison of OOP capacities at different aspect ratios for infills of different heights, thickness, and masonry strengths is kept in Fig 11. Aspect ratio (l/h) (c) by Wang et al (2020) from their numerical study. As an example, the particular case of an infill wall (height =2600 mm) having an aspect ratio of 1.0 is shown in Figs 12-15.…”
Section: Effect Of Aspect Ratiomentioning
confidence: 99%
See 2 more Smart Citations
“…Infills and partitions typically account for a significant part of the total NC costs (Restrepo and Bersofsky 2011). Infills and partitions were extensively studied in the past few decades, and their seismic performance was widely assessed through both experimental testing (Di Fiorino, Bucciero, and Landolfo 2019;Landolfo et al 2019;Magliulo et al 2014;Onat et al 2018;Pali et al 2018;Petrone, Magliulo, and Manfredi 2014;Restrepo and Bersofsky 2011;Tasligedik, Pampanin, and Palermo 2015;Verderame et al 2019) and numerical methods (Petrone et al 2018;Wang et al 2020;Zhai et al 2018). These components are sensitive to interstory drift within their plane (i.e., in-plane (I-P) damage mechanisms) and accelerations along their out-ofplane direction (i.e., out-of-plane (O-O-P) damage mechanisms) (Petrone, Magliulo, and Manfredi 2017).…”
Section: Introductionmentioning
confidence: 99%